2008
DOI: 10.1212/01.wnl.0000326898.05099.04
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal and thalamic atrophy in mild temporal lobe epilepsy

Abstract: The structural abnormalities seen in patients with mild temporal lobe epilepsy (TLE) demonstrate that a temporo-limbic pathway, which includes the thalamus, plays a major role in the pathogenesis of TLE. It is likely that other factors, especially genetic ones, play a major role in the causation and severity of TLE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

24
97
4
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(128 citation statements)
references
References 34 publications
24
97
4
3
Order By: Relevance
“…2,3 Moreover, using voxel-based morphometry and cortical thickness we have confirmed mesial temporal lobe, parietal lobe, and thalamic abnormalities that were remarkably comparable to what is observed in patients with refractory TLE regardless of the presence of Hs. 4,5 Of interest, our observations in benign TLE are consistent with the brain regions reported by Keller et al 1 This finding further enlarges the thalamocortical network being observed, even in patients with very mild epilepsy.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…2,3 Moreover, using voxel-based morphometry and cortical thickness we have confirmed mesial temporal lobe, parietal lobe, and thalamic abnormalities that were remarkably comparable to what is observed in patients with refractory TLE regardless of the presence of Hs. 4,5 Of interest, our observations in benign TLE are consistent with the brain regions reported by Keller et al 1 This finding further enlarges the thalamocortical network being observed, even in patients with very mild epilepsy.…”
supporting
confidence: 92%
“…Moreover and very exciting, we found the same pattern of thalamic damage in patients with benign TLE, without radiologic evidence of Hs and normal hippocampal volumetry. 4,5 All these data 1,[4][5][6][7] support that the thalamus is centrally involved in the epileptogenic network of TLE, as also suggested by postsurgical studies reporting that the prognosis could be related to the extension of the epileptogenic network to the subcortical thalamic structure in TLE. 8 Obviously as Keller et al highlighted, 1 all evidence of thalamic structural abnormalities are derived from T 1 -weighted magnetic resonance imaging (MRI) scans only and details on brain connectivity are still lacking and deserve more attention with larger samples.…”
supporting
confidence: 62%
“…In humans, an image analysis method in which brain volume determined by MR images is analyzed by on a voxel-by-voxel basis (Voxel-Based Morphometry) 29 and another method where the hippocampus area is divided by intracranial area 7,29 are used. Voxel based morphometry requires a database of normal images for comparison.…”
Section: Discussionmentioning
confidence: 99%
“…We also used 3 different advanced structural neuroimaging operator-independent approaches, called shape analysis, 6 voxelbased morphometry, 7,8 and automated hippocampal segmentation (FreeSurfer; http://surfer.nmr.mgh.harvard.edu/) 9,10 to determine whether Hh seen on visual MR imaging could have masked occult atrophy.…”
mentioning
confidence: 99%